The Frontstage and Backstage of Corporate Sustainability Reporting: Evidence from the Arctic National Wildlife Refuge Bill - Charles H. Cho; Matias Laine; Robin W. Roberts; Michelle Rodrigue
Abstract While proponents of sustainability reporting believe in its potential to help corporations be accountable and transparent about their social and environmental impacts, there has been growing criticism asserting that such reporting schemes are utilized primarily as impression management tools. Drawing on Goffman’s (The presentation of self in everyday life, Doubleday, New York, 1959) self-presentation theory and its frontstage/backstage analogy, we contrast the frontstage sustainability discourse of a sample of large U.S. oil and gas firms to their backstage corporate political activities in the context of the passage of the American-Made Energy and Good Jobs Act, also known as the Arctic National Wildlife Refuge (ANWR) Bill. The ANWR Bill was designed to allow oil exploration within the most sensitive environmental areas in the Refuge and this bill was vigorously debated in the United States Congress in 2005 and 2006. Our results suggest that the firms’ sustainability discourse on environmental stewardship and responsibility contrasts sharply with their less visible but proactive political strategies targeted to facilitate the passage of the ANWR Bill. This study thus contributes to the social and environmental accounting and accountability literature by highlighting the relevance of Goffman’s frontstage/backstage analogy in uncovering and documenting further the deceptive nature of the discourse contained in stand-alone sustainability reports. In addition, it seeks to contribute to the overall understanding of the multifaceted nature of sustainability reporting by placing it in relation to corporate political activities. Backstage and frontstage, Goffman, Impression management, Lobbying and political strategies, Self-presentation, Sustainability reporting